Chinese fiction of the nineteenth and early twentieth centuries : essays - Hanan, Patrick (Masters of Chinese studies, 2004)
"It has often been said that the nineteenth century was a relatively stagnant period for Chinese fiction, but preeminent scholar Patrick Hanan shows that the opposite is true: the finest novels of the nineteenth century show a constant experimentation and evolution. In this collection of detailed and insightful essays, Hanan examines Chinese fiction before and during the period in which Chinese writers first came into contact with western fiction."--Jacket.